The antipoverty effectiveness of child support: Empirical evidence for Latin American countries - Laura Cuesta; Mia Hakovirta; Merita Jokela (Luxembourg Income Study (LIS), 2018)
In this paper we examine the role of child support in the economic well-being of children in single-parent families in Latin America. We use the Luxembourg Income Study wave IX and the 2012 Colombian Quality of Life Survey to answer three questions: (1) are children in single-parent families more likely to be poor than children in two-parent families? (2) what is the relative importance of different income sources in the income packages of these families? and (3) are child support transfers improving the economic well-being of children in single-parent families? Our results show that children in single-parent families are disproportionally poor relative to two-parent families in Brazil, Colombia, Panama, Paraguay, and Uruguay. For other countries, poverty rates are similar (Guatemala and Peru), or higher in two-parent families than single-parent families (Mexico). Labor income is the most important income source for both types of families in all of these countries. However, child support represents between 20 and 39 per cent of total income among families receiving this transfer. The largest antipoverty effectiveness of child support is also observed among these families. Child support brings between 30 and 55 per cent of children receiving this transfer out of poverty.
Keywords: 330